Digitizing Master Engineering Documents - Rina Wijayanti; Gancar Candra Premananto (Budapest International Research and Critics University, 2022)
The main function of division Master Engineering Documents of the Design and Development Department is to store and maintain technical documents for all PGs. The work will increase every year, the documents stored will also continue to grow. The large number of documents in the form of hard files stored in the “Dokumen Teknik Induk” building makes it difficult for staff in the management process, both when searching for documents and maintaining them. In the document management process, it is necessary to have a master data that can accommodate all soft file documents. In addition to facilitating the process of data maintenance and document management, the existence of a master data document in the form of a softfile will make it easier for staff during the document search process according to user needs, the data distribution process will also become more effective.